Effectiveness of Digital Reproductive Health Education Interventions for Adolescent Girls: A Literature Review - Yusuf, Nurlathifah N.; Yanti, Eka Mustika; Nafi, Joice Deby (JURNAL KESEHATAN TROPIS INDONESIA, 2026)
Reproductive health education is a critical need for adolescent girls who face various sexual and reproductive health risks, while access to comprehensive education remains limited. Advances in digital technology offer new opportunities through digital-based educational interventions that are more flexible and accessible. This study aims to evaluate the effectiveness of digital reproductive health education interventions for adolescent girls and to identify factors influencing their effectiveness. The method used was a literature review of studies employing randomized controlled trial designs that assessed various digital interventions, including mobile applications, text messaging, educational games, and entertainment-based videos. The findings indicate that digital interventions consistently improve adolescent girls’ knowledge and attitudes toward reproductive health and enhance their confidence in accessing health services. However, changes in risky sexual behaviors and long-term contraceptive use remain limited. The implications of this study suggest that digital interventions should be integrated with supportive approaches, such as family involvement and continuous follow-up, to achieve more effective and sustainable behavioral change.